The etiology and clinical features of non-CAH primary adrenal insufficiency in children - Liu, Ziqin; Liu, Yi; Gao, Kang; Chen, Xiaobo (Frontiers in Pediatrics, 2022)
Background: The most common cause of primary adrenal insufficiency (PAI) in children is congenital adrenal hyperplasia; however, other genetic causes occur. There is limited epidemiological and clinical information regarding non-CAH PAI. Methods: Data for patients diagnosed from January 2015 to December 2021 at a tertiary hospital in northern China were retrospectively analyzed. We excluded those with CAH, which is the most common pathogenic disease among PAI patients. Next-generation sequencing was used for genetic analysis. Results: This retrospective study included 16 children (14 males and 2 females) with PAI. A genetic diagnosis was obtained for 14/16 (87.5%) individuals. Pathogenic variants occurred in 6 genes, including ABCD1 (6/16, 37.5%), NR0B1 (4/16, 25.0%), NR5A1/steroidogenic factor-1 (2/16; 12.5%), AAAS (1/16, 6.25%), and NNT (1/16, 6.25%). No genetic cause of PAI diagnosis was found in 2 girls (2/16, 12.5%). Conclusions: Causes of PAI in children are diverse and predominantly affect males. Most PAI in children is congenital, and ABCD1 gene defects account for the largest proportion of PAI cases. Whole-exome sequencing is a tool for diagnosis. However, diagnoses are unclear in some cases.